STRATEGI KOMUNIKASI BNN DALAM MENSOSIALISASIKAN PROGRAM P4GN DALAM BIDANG PENCEGAHAN DI KOTA DENPASAR - Marheni, Ade Novi; Alit Suryawati, I Gusti Agung; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT Through the P4GN program (Prevention, Eradication, Illicit Abuse and Circulation of Narcotics) the National Narcotics Agency continues to try to tackle drug problems by carrying out basic tasks and functions in running this program in a comprehensive and multidisciplinary manner. This study aims to determine the communication strategies implemented by the National Narcotics Agency (BNN) in disseminating the P4GN program (Prevention, Eradication, Illegal Abuse and Circulation of Drugs) in the City of Denpasar. This study uses qualitative research methods using data collection techniques semi-structured interviews, observation, and documentation studies. Based on the findings in the field, it can be seen that the National Narcotics Agency (BNN) in disseminating the P4GN program (Prevention, Eradication, Misuse and Illicit Circulation of Drugs) in the field of prevention uses several steps in formulating communication strategies, starting from knowing audiences, arranging messages, setting methods, to select media usage. Keywords: BNN, P4GN Program, Field of Prevention, Communication Strategy.